Evaluation of turmeric (Curcuma longa L.) genotypes for yield attributes, yield and reaction to foliar diseases - Singh, A K (Journal of Spices and Aromatic Crops, 2013)
An experiment was conducted during 2005–06 to 2008–09 at Raigarh (Chhattisgarh) to assess the variability of thirteen genotypes of turmeric for yield and disease resistance. The results indicated that entries TCP-11 and TCP-82 produced maximum yield i.e, 20.3 and 18.8 t ha-1, respectively. Entry TCP-11 showed resistance to leaf spot and blotch while TCP-82 was found to be moderately resistant to Colletotrichum leaf spot and resistant to Taphrina leaf blotch. The check variety IISR Prabha showed moderate resistance to both the diseases and yielded 14.4 t ha-1.